ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN INDIVIDU MELAKUKAN FRAUD DALAM PERSPEKTIF FRAUD PENTAGON BERDASARKAN PERSEPSI PEGAWAI INSTANSI PEMERINTAHAN KABUPATEN BREBES - Maulana, Rizki; Mubtadi, Novendi Arkham (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
This study aims to examine the effect of fraud pentagon on fraud at government sector in Brebes regency. The population of this study is all employess at government in Brebes regency. The sample selection is conducted through purposive sampling method. The total sample is 110 respondens. The analysis method used in this study is multiple regression analysis. The results of this study show that leadership style has a negative and significant effectÂ on fraud in government, internal control system has a positive and significant effect on fraud in government, organizational culture has a negative and significant effect on fraud in government, individual morality has no effect on fraud in government, competence has a positive and significant effect on fraud in government, and dualism of position has a positive and significant effect on fraud in government.